Mouse LIMR3/CD300f is a negative regulator of the antimicrobial activity of neutrophils. Issue 1 (December 2018) - Ueno, Keigo; Urai, Makoto; Izawa, Kumi; Otani, Yoshiko; Yanagihara, Nao; Kataoka, Michiyo; Takatsuka, Shogo; Abe, Masahiro; Hasegawa, Hideki; Shimizu, Kiminori; Kitamura, Toshio; Kitaura, Jiro; et al.
Abstract Leukocyte mono-immunoglobulin-like receptor (LMIR)/CD300 proteins comprise a family of immunoglobulin-like receptors that are widely expressed on the immune cell surface in humans and mice. In general, LMIR3/CD300f suppresses the inflammatory response, but it can occasionally promote it. However, the precise roles of LMIR3 in the function of neutrophils remain to be elucidated. In the present study, we investigated LMIR3 expression in mature and immature neutrophils, and evaluated the effects of LMIR3 deficiency in mouse neutrophils. Our results indicated that bone marrow (BM) neutrophils expressed LMIR3 on their cell surface during cell maturation and that surface LMIR3 expression increased in response toPseudomonas aeruginosa infection in a TLR4/MyD88-dependent manner. LMIR3-knockout (KO) neutrophils displayed significantly increased hypochlorous acid production, and elastase release, as well as significantly augmented cytotoxic activity againstP .aeruginosa andCandida albicans ; meanwhile, inhibitors of elastase and myeloperoxidase offset this enhanced antimicrobial activity. Furthermore, LMIR3-KO mice were significantly more resistant toPseudomonas peritonitis and systemic candidiasis, although this may not be entirely due to the enhanced activity of neutrophils. These results demonstrate that LMIR3/CD300f deficiency augments the antimicrobial activity of mouse neutrophils.